Genetic Stability of Banana Plant Regenerated from Floral Axis Organogenesis Assessed by Newly Developed SSR Markers - Puji Lestari; I. Roostika; Kristianto Nugroho; Edison HS; Habib Rijzaani; Mastur Mastur (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Molecular marker is robust to precisely monitor the genetic stability of in vitro-banana plants. This study examined the genetic stability of 8 monthold banana plants of Soka variety derived from floral axis organogenesis using newly developed SSR markers. The results showed that the same qualitative and similar quantitative morphological characters of pseudostem, leaf and fruit were identified between mother plants and culture plants from floral axis regeneration. Both plants types were quite similar in number of tillers, brix percentage, fruit peel/mesocarp thickness and fruit length. Eleven out of 211 good quality of SSR loci showing high homology with important genes were selected for suitable PCR primers and produced unambiguous bands.The number of total bands was 323 for total SSR primers, in range of 20-60 per primer for total individual plants. Most culture plants showed identical with their mother plants, with very minor variation as reflected by genetic similarity coefficient range of 0.9-1.0. A high similar pattern on SSR to support morphological characters of mother plants and culture plants indicated a successful micropropagation using floral axis to encounter off-type clones.The floral axis organogenesis in this study is able to provide sufficient genetic materials of Soka for varietal registration and other applications.